KENYAMANAN TERMAL DALAM RUANG PERTEMUAN UMUM DITINJAU DARI ASPEK SIRKULASI UDARA: Studi Kasus Handep Hapakat Kabupaten Pulang Pisau - Mardika, I Kadek; Sagala, Daniel (JURNAL PERSPEKTIF ARSITEKTUR, 2023)
Good air circulation is needed in a naturally ventilated room to achieve thermal comfort because it can speed up the heat dissipation process and the availability of fresh air in the room. This study aims to examine the air circulation of the meeting room at the Handep Hapakat General ` Kenyamanan termal dalam ruang Pertemuan Umum Handep Hapakat Kabupaten Pulang Pisau ditinjau dari Aspek Sirkulasi Udara 2 Meeting Building in Pulang Pisau Regency and the factors that affect the thermal comfort of the building. This study used descriptive qualitative method. The independent variables were obtained through field measurements in the form of meeting room dimensions, type and area of ventilation openings, while the dependent variable in the form of microclimate included wind speed, indoor and out door temperatures, and air humidity. The analysis was carried out to find out which parts of the room experienced high and low airflow and to find out the supporting factors and obstacles by using the HTC-2 Thermometer Hygrometer and Digital Wind Anemometer GM 816 tester. The results showed that the ventilation system and the type of opening distributed comfortable air movement or wind speed in the space between 0.1 m/s to 0.5 m/s with an air humidity of 49% - 52%, with a ratio of ventilation openings (11 %) of the floor area of the room. It was concluded that the ratio of the opening area to the meeting room area was good enough so that the air circulation was quite smooth.